Handbook of bioelectronics - Carrara, Sandro; Iniewski, Krzysztof, 1960- (Cambridge : Cambridge University Press, 2015)
This wide-ranging summary of bioelectronics provides the state of the art in electronics integrated and interfaced with biological systems in one single book. It is a perfect reference for those involved in developing future distributed diagnostic devices, from smart bio-phones that will monitor our health status to new electronic devices serving our bodies and embedded in our clothes or under our skin. All chapters are written by pioneers and authorities in the key branches of bioelectronics and provide examples of real-word applications and step-by-step design details. Through expert guidance, you will learn how to design complex circuits whilst cutting design time and cost and avoiding mistakes, misunderstandings, and pitfalls. An exhaustive set of recently developed devices is also covered, providing the implementation details and inspiration for innovating new solutions and devices. This all-inclusive reference is ideal for researchers in electronics, bio/nanotechnology, and applied physics, as well as circuit and system-level designers in industry.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Medical electronics; Biotechnology; Biomedical engineering